TV privada de acesso amplo X TV pública de acesso restrito: desafios contemporâneos da comunicação pública brasileira - Rabêlo, Melissa Silva Moreira (2016)
Thesis about the contemporary challenges in the Brazilian public communication, in contrast to the vast access to private TV versus the restrict access to public TV, that brings concerns originated from the studies of Communication Policies and Political Communications Economics during the development of Master dissertation, entitled: THE RELATIONSHIP BETWEEN PUBLIC AND PRIVATE IN THE PUBLIC FIELD OF COMMUNICATION IN BRAZIL: the experiences of TV Cultura and TV Brasil. It is intended, therefore, to examine the conditions of access to the Brazilian public TV, as opposed to the Private TV, before the technological progress of the field, able to ensure the democratization in the field. Therefore, it was developed a documental bibliographic research and a field research, having as contributions, the studies made during the period of the “sandwich” doctorate (PhD) program at the Syracuse University NY/USA, within the evaluation of public policies, with a process appraisal. In the evaluation, the discussion about the relationship between public and private in the public field of communication in Brazil is revisited and is made an in depth analysis, added to the discussion about public field, hegemony and cultural industry, categories that give a conceptual base to the qualitative approach of the research. Discusses about this relationship considering the hegemony of the private system of communication and it´s relationship with the State, as well as, the principles and challenges of the public system. It is presented discussions about public space versus private interests, in addition to discussing the regulations of the field. Thus, it is intended to propose alternative changes of such paradigms, through theoretical discussion and presentation of the field research data with technological innovations in contemporary times, being an important contribution.